( 6 + x)(9 + x) =88
54 + 15x + x^2 = 88
x^2 + 15x - 34 = 0
(x + 17)(x - 2) = 0
using zero product property:-
x + 17 = 0 or x - 2 = 0 giving:-
x = -17 , x = 2
x is the amount that the length and width are increased by.
x = -17 is negative and doesn't make sense in this context and can be ignored; so the amount of increase is 2 feet.
Answer:
A
Step-by-step explanation:
To find (f ○ g)(x) substitute x = g(x) into f(x), that is
f(g(x))
= f(2x - 1)
= 3(2x - 1) + 14
= 6x - 3 + 14
= 6x + 11 → A
Take the derivative, then plug in any number in the domain. If the number is positive the function is decreasing, if it's negative it's decreasing.